An exploratory multivariate study examining correlates of trait mental and physical fatigue and energy. Issue 1 (2nd January 2019) - Boolani, Ali; Manierre, Matt
ABSTRACT: Background: Mental and physical energy and fatigue can be assessed as either stable long-term traits or as a temporary state. Although researchers recognize the need to separate the two, most research has focused on state, leaving trait understudied. Therefore, the objective of this study was to apply demographic, lifestyle and psychosocial variables known to be associated with state fatigue and energy to examine predictors of trait mental and physical energy and fatigue. Methods: A convenience sample (N = 671) completed an online survey measuring mood, physical activity, mental workload, polyphenol (plant-based healthy micronutrients) consumption in the diet, and sleep quality. A multivariate multiple regression model was fit to simultaneously test associations between covariates for each four trait fatigue indicators. Results: Poor sleep quality was the only consistent predictor of both energy and fatigue (mental and physical), with confusion correlating with all but physical energy. Age and depression were predictors of mental and physical fatigue, but caffeine consumption was predicted by higher physical fatigue only. Mental workload and physical activity on off-days predicted physical energy only, while polyphenol consumption and BMI predicted mental energy only. Conclusions: Findings suggest that mental/ physical energy and fatigue may be separate constructs that can be treated as empirically distinct. The distinctions between physical and mental fatigue are less pronounced, needing further exploration. Subsequent research should explore other potentially important biopsychosocial sources of variation in trait mental and physical energy and fatigue.